The Use of Ultrasound-Measured Optic Nerve Sheath Diameter to Predict Ventriculoperitoneal Shunt Failure in Children. Issue 4 (April 2019) - Lin, Sophia D.; Kahne, Kimberly R.; El Sherif, Amira; Mennitt, Kevin; Kessler, David; Ward, Mary J.; Platt, Shari L.
Abstract : Objective: The goal of this study was to assess the accuracy of ultrasound-measured optic nerve sheath diameter (ONSD) as a screen for ventriculoperitoneal shunt failure. Methods: We prospectively enrolled a convenience sample of children presenting to the ED with suspected shunt failure. The ONSD was measured by ultrasound and compared with computed tomography/magnetic resonance imaging (CT/MRI) and neurosurgical impression. We defined shunt failure on ultrasound as an ONSD greater than 4.0 mm in infants 12 months and younger or greater than 4.5 mm in children older than 12 months. A single emergency radiologist at our institution read all CTs and MRIs for categorical determination of shunt failure. We defined shunt failure based on neurosurgical impression as a decision to admit and perform shunt revision. We report test characteristics and 95% confidence intervals of ONSD as a predictor for shunt failure. Results: We enrolled 32 subjects. The sensitivities of ONSD compared with CT/MRI and neurosurgical impression, 60.0% and 75.0%, respectively, were low. However, the negative predictive values of ONSD compared with CT/MRI and neurosurgical impression were 90.0% and 95.0%, respectively. Conclusions: Optic nerve sonography may be a useful tool to identify children presenting with suspected ventriculoperitoneal shunt failure who do not require further imaging. This would reduce the use of CT scan and exposure to ionizing radiation in children with suspected shunt malfunction who do not require neurosurgical intervention. Consideration of additional risk factors and a larger sample size may yield stronger results.